1998
DOI: 10.1002/cbm.209
|View full text |Cite
|
Sign up to set email alerts
|

Adult criminality in previously hospitalized child psychiatric patients: with particular reference to girls and the use of ICD‐10 diagnoses

Abstract: A total of 171 children admitted to a psychiatric inpatient unit before age 13 were examined, between 1967 and 1980, using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Women who had experienced family disruption in childhood, and spent periods in institutional care, were at markedly increased risk of involvement in crime. Wright et al (1998) also identified reception into public care as a key risk factor for offending among girls in a clinically referred sample, as did a Home Office report on imprisoned women, where 35% had been in care (Caddle and Crisp, 1997). Reception into care and institutional rearing undoubtedly index a range of more specific risk pathways.…”
Section: Discussionmentioning
confidence: 94%
“…Women who had experienced family disruption in childhood, and spent periods in institutional care, were at markedly increased risk of involvement in crime. Wright et al (1998) also identified reception into public care as a key risk factor for offending among girls in a clinically referred sample, as did a Home Office report on imprisoned women, where 35% had been in care (Caddle and Crisp, 1997). Reception into care and institutional rearing undoubtedly index a range of more specific risk pathways.…”
Section: Discussionmentioning
confidence: 94%